ANALISIS TERHADAP PEMBERHENTIAN APARATUR SIPIL NEGARA SECARA TIDAK HORMAT AKIBAT DIKELUARKANNYA SURAT KEPUTUSAN BERSAMA (SKB) 3 MENTERI (STUDI KASUS PUTUSAN NO. 9/6/2019/PTUN-TPI) - Twini Nurul Ariestiani; Ahmad Redi (Fakultas Hukum Universitas Tarumanagara, 2021)
Government employees play a vital part in their obligations and specialists, for the accomplishment of carrying out government and advancement undertakings to accomplish public objectives. This goal has been directed in the Overall arrangements of Article 10 of Law no. 5 of 2014 concerning Civil Servant, In this investigation utilizing regularizing juridical by observational examination. This exploration utilizes a legal methodology, an idea approach and a case approach. The aftereffects of this investigation demonstrate that lawful choices that are restricting on the Joint Pronouncement (SKB) of the Pastor of Home Undertakings, MENPAN and RB, and the Head of BKN Number 182/6597/SJ, Guideline Number 15 of 2018 or 153/KEP/2018, to the Common Help Administrative Official doesn't have restricting lawful power by and large, it's simply that this Joint Announcement stays restricting for the Staff Directing Official and the Authority approved to uphold the law for this situation disgraceful excusal. Legitimate insurance to Civil Servant assembly for despicable release in Court Choice Number 9/G/2019/PTUN-TPI has not been completely acquired for ASN for this situation. From the above case, which started with a criminal demonstration of defilement by the convict/culprit, to Civil Servant Rivana, ST, he has been authorized through losing his employment and his compensation as a Government worker. The litigant/culprit, to be specific that Rivana, ST, has been condemned to detainment for 1 (one) year and 4 (four) months as expressed by the Tanjungpinang Locale Court No. 412/PID.B/2008/PN.TPI which has extremely durable lawful power on February 18, 2009